REPRESENTASI POLA KOMUNIKASI DALAM BUDAYA BATAK DI FILM NGERI-NGERI SEDAP - Sarah Nur Humairoh (2023)
Film is a communication medium that can describe a story so that it can be enjoyed by audiences and a medium for delivering messages. Like a phenomenon in a society or a family that has meaning. One of them is a film about a family with a cultural background, namely the film Ngeri-Ngeri Sedap. This study aims to find an overview of communication patterns within a family with a Batak ethnic background in film media, namely the film Ngeri-Ngeri Sedap. The method used in this research is descriptive qualitative with Roland Barthes's semiotic analysis approach to find out the meaning of denotation, connotation and myth. The results of the study show that this film can describe several patterns of family communication in Batak culture in the film Ngeri-Ngeri Sedap including conflict and interrelated cultural communication. There are several patterns of family communication that dominate, namely the equality pattern of family communication, the unbalanced split pattern of communication, and the monopoly pattern of communication. The pattern of communication that exists in Pak Domu's family is dominated by parents in making decisions. This can be influenced by the culture in the family, namely the Batak culture.